MORFOLOGI PASAK BUMI (Eurycoma spp) DI DUSUN BENUAH KABUPATEN KUBU RAYA KALIMANTAN BARAT - Setyaningrum, Dina; Kartikawati, S M; Wahdina, . (Universitas Tanjungpura, 2017)
Pasak bumi is an Indonesian endemic plants and just grow in Sumatera and Kalimantan. This study aimed to know how the morphology of pasak bumi by measuring of radiks, folium, caulis and flos. The method of this study were observing the radiks (radiks system, size, type), caulis (type, size, colour), folium (total of folium compositum, totally long of folium compositum, rachis, totally of foliolum, and foliolum observed are circumscriptio, apex folii, basis folii, nervatio or venatio, margo folii, intervenium, colour, and surface), and flos (totally flos, calyx, sepal, statemen,Â tassel, female flowers). The results showed that the pasak bumi have grow in Dusun Benuah Kabupaten Kubu Raya West Kalimantan is a rarely shrubs or treelets and a spesies of Eurycoma longifolia Jack. Characteristic of Pasak bumi are 140 cm height, and 0,54 cm diameter. The caulis colour is brown to grey and monopodial. Folium compositum is imparipinnate, circumscriptio is ovate-lanceolate to obovate-lanceolate, apex folii is subacute or acute to acuminate, margo folii is integer. The flos of pasak bumi is inflorescentia ramosa panicula, panicles axillary, which has 46Â flowers. The radiks of pasak bumi is a radix primaria. Keywords: Eurycoma longifolia Jack., morfologi, pasak bumi.